Isolation and Screening of Antimicrobial Producing-Actinomycetes Symbionts in Nudibranch - R. Riyanti; Jaka Widada; Ocky Karna Rajasa (Universitas Gadjah Mada, 2009)
The aims of this study were to isolate and to screen actinomycetes associated with sea slug which have the ability to produce antimicrobial compound, especially against MDR strains. Actinomycetes were isolated from nudibranchs collected from Bandengan coastal waters and the Panjang island, Jepara, Central Java. Actinomycete isolates were assayed for their antimicrobial activity against MDR strains (MDR 6 E. coli, MDR 7 Enterobacter sp., MDR 13 Proteus sp., MDR 14 Staphylococcus sp.). The genetic diversity of the active isolates was analyzed by using repetitive DNA fingerprinting. Antimicrobial activity was also performed on the ethyl acetate bacterial extract. The amplification of Polyketide Synthase-I (PKS-I) and Non-Ribosomal Peptide Synthetase (NRPS) genes was carried out to estimate the genetic potency of actinomycetes. The most active actinomycete isolate was sequenced based on 16S rDNA approach. General profile of antimicrobial substances was analyzed by using Thin Layer Chromatography (TLC). A total 27 isolates were obtained from nudibranchs Jorunna sp. and 12 isolates from Chromodoris sp. Ten isolates exhibited antimicrobial activity. Five representative isolates were selected based on rep-PCR analysis. Three ethyl acetate extracts exhibited antimicrobial activity against MDR 7, MDR 13, and MDR 14, except MDR 6. NPC 8 isolates significantly inhibited the growth of the tested strain and amplified NRPS gene fragment. Molecular identification revealed that isolate NPC 8 closely related to Streptomyces sp with a high homology of 96%.